Export Orientation and Productivity in Sub-Saharan Africa - Pattillo, Catherine (IMF Working Papers; Working Paper ;, 2002)
Analysis of firm-level panel data from three sub-Saharan African economies shows that exporting manufacturers have a total factor productivity premium of 11-28 percent. The data do not allow testing of whether these premiums are caused by selection of more efficient producers into exporting or by learning-by-exporting. By thinking about the mechanisms behind selectivity and learning, however, our finding of higher premiums for direct exporters and exporters to outside Africa could be interpreted as being consistent with learning-by-exporting effects. However, if learning-by-exporting is indeed present in the data, we cannot disentangle its effect on productivity from those of more traditionally recognized channels of international technology diffusion.